2021
DOI: 10.1080/23311932.2021.1950402
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment of three baled rice straw varieties intended for use as ruminant feed in Namibia

Abstract: This study determined and compared the proximate and chemical composition of Angola, IRGA 418 and SUPA rice straw varieties harvested and baled in 2016 and 2017. In both 2016 and 2017, SUPA straw had the highest dry matter (DM) content (960.7 ± 0.50 g/kg and 939.4 ± 0.10 g/kg), neutral detergent fibre (NDF) (575.2 ± 9.90 g/kg and 594.7 ± 9.00 g/kg), acid detergent fibre (ADF) levels (374.7 ± 6.30 g/kg and 379.9 ± 9.90 g/kg) and cellulose (CL) content. Angola straw had the highest crude protein (CP) content (39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition to its many uses in the food and beverage industries, lactic acid and its derivatives also have a wide range of applications in the pharmaceutical, cosmetic, and manufacturing industries [91,92]. Numerous studies have demonstrated that rice straw can be utilized to make second-generation biofuels [47,[93][94][95][96]. Typically, bacteria and yeast turn carbohydrates into lactic acid and sugars into alcohol.…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
“…In addition to its many uses in the food and beverage industries, lactic acid and its derivatives also have a wide range of applications in the pharmaceutical, cosmetic, and manufacturing industries [91,92]. Numerous studies have demonstrated that rice straw can be utilized to make second-generation biofuels [47,[93][94][95][96]. Typically, bacteria and yeast turn carbohydrates into lactic acid and sugars into alcohol.…”
Section: Composition Of Rice Huskmentioning
confidence: 99%